Mechanism and Energy Evolution Characteristics of Coal Burst in Mining Thick, Deep, and Large Inclined Coal Seams: A Case Study from a Chinese Coal Mine - Chengchun Xue; Anye Cao; Wenhao Guo; Yaoqi Liu; Songwei Wang; Jingyuan Dong; Yu Gu (Geofluids)
Coal burst is a severe and dynamic hazard, and understanding its mechanism is crucial in preventing such incidents. Strong tremors during the working face mining in the stress anomaly zone of the pinch-out coal seam are frequent. Theoretical analysis, numerical simulation, and field measurement methods are used to analyze the energy evolution law for mining at the working face and mechanism of coal burst. Mechanical models of the inclined and strike overhang structures are established, and the theoretical analysis of the strike and inclined energy distribution characteristics of the working face roof is carried out. The two key areas with a high overhang bending deformation energy accumulation are identified at the lower end and middle-upper part of the working face. The simulation results show that the energy accumulation area of the roof in the inclined coal seam has prominent asymmetric distribution characteristics. The roof energy accumulates in the lower end and middle-upper area of the working face. The floor energy accumulates in the lower end area of the working face, and the peak position of the overhead energy of the working face in the direction shifts toward the coal-wall side. Influenced by the local absence of the No. 8 coal seam, the vertical stress of the surrounding rock at the working face of the massive, inclined coal seam increased by 12.7%; the peak of roof energy at the working face inclination and strike increased by 46.2% and 32.2%; and the range of roof energy accumulation expanded. A deep directional hole blasting plan to prevent the phenomenon at the working face roof is developed, which effectively reduces the stress and energy level of the inclined hanging roof and avoids the occurrence of coal bursts in the abnormal stress area of the working face.